Lightweight design optimization of a bow riser in Olympic archery applying evolutionary computing - Edelmann-Nusser, J.; Heller, M.; Clement, S.; Vajna, S.; Jordan, A. (European Journal of Sport Science, 2004)
Recurve bows that are used in competitions like the Olympic Games are high-technology products. Good risers are lightweight but retain a high stiffness. The aim of this study was to design a riser with a stiffness comparable to that of the lightest riser currently used by the archers of the German National Archery Team, but with a considerably reduced weight. We computed the loads that are applied to a riser of a drawn recurve bow (the RADIAN model used by the German team) and created a 3-D solid CAD model of a riser with 24 variable parameters. We used evolutionary computing to optimize the 24 parameters of the model according to these criteria. We selected the most optimal riser out of the 1650 CAD models generated, manufactured it, and had it tested by three archers of the German National Archery Team. The mass of our manufactured riser is 871g, which is 243g or 22% less mass than the RADIAN riser.